Pedagogic Competence of Lecturers: The Key to Success in Inclusive Education in Religious Universities - Urbanus Sukri (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study explores the pedagogical competence of lecturers as a key factor in the success of inclusive education in religious higher education institutions. Novelty: The study addresses unique challenges in religious academic settings, such as balancing religious values with inclusivity, adapting curricula, and fostering an inclusive culture—a perspective underexplored in existing literature. Methods: Using a qualitative approach through literature review and library research, this study examines various academic sources to identify essential elements of pedagogical competence for inclusive education. Results: The findings reveal that pedagogical competence includes curriculum adaptation, innovative teaching strategies, student-centered learning, and sensitivity to diverse student needs. The study underscores the importance of professional development, institutional support, and policy frameworks to promote inclusivity. Conclusion: By enhancing pedagogical competence, lecturers can create inclusive learning environments for students with diverse backgrounds and abilities. This study contributes to higher education inclusivity discourse by emphasizing the role of pedagogical skills in equitable education. Future research should validate these findings through empirical case studies in religious higher education settings.